KEPARIWISATAAN ALAM MERESPON TANTANGAN PERUBAHAN IKLIM Studi Kasus di Taman Nasional Tanjung Putting - Johan Setiawan (JURNAL NASIONAL PARIWISATA, 2012)
Climate may affect the quality and type of tourism activities that developed within a region. There are some natural tourism resources which is very vulnerable toward direct and indirect impacts of the climate change threats. Increased extremely temperatures and also the changes in length of winter or summer may affect visitors length of stay. On the other hand, tourism may contribute to global warming through gas emissions from transportation, accommodation and other related tourism activities. In 2005 UNWTO predict if the tourism business is run as ‘business-as-usual’ scenario, there is no any response or adaptation program, that predicted in 2035 the emissions produced from tourism sector will increase 161% higher than today. Considering these facts, UNWTO invites overall stakeholders of individual to the State level responding to the climate change phenomena by implementing adaptation program in order to reduce greenhouse gas emissions and preventing global warming threats. This study aims to understand the characteristics of visitor typology and their points of view toward the climate change phenomena. It is also purposed to explore and assess adaptation program that can be developed in Tanjung Puting National Park (TPNP) based on their perspective. The results of this study are as follows: (1). the tourism market of TPNP has a feature of ‘eco-tourist’ with a high awareness and concern towards environ-mental issues, including the threat of climate change phenomena. Visitors of TPNP have a high ethical manner for nature and local culture. Generally, the visitors also have a higher education and income, which is very potential to engage them into an environ-mental conservation, (2). The visitors of TPNP realize that climate change is a serious challenge and need a concrete action. Some adaptation program desired by the visitors are fund raising program for Orangutan conservation and its habitat. The visitors are likely willing to give a donation Rp.172,000.00/visitor. Such concept of the donation is a mechanism of offset emissions generated due their visits by providing funds for conser-vation efforts. The visitors encourage managers of the destination for improvisation and technology investment in the boat (kelotok) machine which as the machine is efficient and less noisy. The visitors also encourage TPNP authority to limit the number of visitors in order to protect the tourism resource of TPNP and maintain the quality of visits; (3). The visitors were unwilling joined with other guests into any public boat of a larger capacity, in order to keep fuel efficiency and GHG mitigation. Merging the visitors traveling with another group instead reducing quality of their trip in Tanjung Puting National Park (TPNP). The visitors are also unwilling to engage in any plantation activities in destina-tion during their visit.